Pengaruh Corporate Social Responsibility (Csr) Terhadap Peningkatan Ekonomi Masyarakat Kelurahan Martajaya Kabupaten Pasangkayu - Rifayanti; Gifa Rahma; Fiona R.H Asal; Nurul Aulia; Siska Amaliah; najwa; Tri Cahya Randani; Almira K. Lahiya; Annisa Prastika Qur'ani; Kusmiатun Khoiriyah; Muzakir Tawil; Rachmad; Askar Mayusa; Nawawi Natsir (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the implementation of the Corporate Social Responsibility (CSR) program by PT Astra Group together with PT Tanjung Sarana Lestari (TSL) and its influence on the economic improvement of the Martajaya Village community, Pasangkayu Regency, West Sulawesi Province. The research was conducted as part of the Field Experience Practice (PPL) activity of the Public Administration Study Program at Tadulako University on May 8–9, 2026. The study employed a descriptive qualitative approach, with data collected through in-depth interviews and documentation studies. Research informants consisted of representatives from the Human Resource Development and Administration (HRDA) division of PT Astra Group and PT TSL, as well as the Secretary of Martajaya Village. The findings reveal that the company's CSR program is implemented through four main pillars—health, education, economy, and environment with the economic pillar designated as the primary priority. The flagship program under the economic pillar is Astra Kreatif, which encompasses micro, small, and medium enterprise (MSME) empowerment, livestock and fisheries sector development, and women's group empowerment. These programs have made positive contributions to community economic development through a village-based coordination mechanism that serves as a bridge between the company and the community. Nevertheless, program implementation still faces five major obstacles: limited public information transparency, minimal community participation in the program planning stage, cultural barriers arising from ethnic heterogeneity, limited geographic reach of the program's target areas, and weak inter-agency coordination. Recommended solutions include adopting an open CSR reporting system, applying a Participatory Program Planning approach, strengthening local wisdom-based strategies, expanding target areas with improved targeting mechanisms, and establishing a structured Multi-Stakeholder Partnership Forum. This study concludes that the effectiveness of CSR as an instrument of community economic empowerment requires program governance that is transparent, participatory, inclusive, and sustainably integrated with regional government development programs.